2008
DOI: 10.1021/es800615f
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and Chromium Partitioning in a Podzolic Soil Contaminated by Chromated Copper Arsenate

Abstract: This research combined the use of selective extractions and x-ray spectroscopy to examine the fate of As and Cr in a podzolic soil contaminated by chromated copper arsenate (CCA). Iron was enriched in the upper 30 cm due to a previous one-time treatment of the soil with Fe(II). High oxalate-soluble Al concentrations in the Bs horizon of the soil and micro-XRD data indicated the presence of short-range ordered aluminosilicates (i.e. proto-imogolite allophane, PIA). In the surface layers, Cr, as Cr(III), was par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Consequently the EXAFS interpretation implies that arsenate was primarily complexed to aluminum hydroxides in the AsUNT and that surface complexation to both aluminum and that iron (hydr)oxide was important in AsZVI. It is well known that arsenate adsorbs strongly to both aluminum and iron (hydr)oxides in soil (Hopp et al, 2008;Manning, 2005) and both are stable at the pH (almost 8) of the samples. Oxalate-extractable aluminum and iron (Table 1) indicated about 1/3 iron and 2/3 aluminum (hydr)oxides in AsUNT while the relation was the opposite, 2/3 iron and 1/3 aluminum (hydr)oxides in AsZVI which agrees well with the EXAFS interpretations.…”
Section: Immobilization Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently the EXAFS interpretation implies that arsenate was primarily complexed to aluminum hydroxides in the AsUNT and that surface complexation to both aluminum and that iron (hydr)oxide was important in AsZVI. It is well known that arsenate adsorbs strongly to both aluminum and iron (hydr)oxides in soil (Hopp et al, 2008;Manning, 2005) and both are stable at the pH (almost 8) of the samples. Oxalate-extractable aluminum and iron (Table 1) indicated about 1/3 iron and 2/3 aluminum (hydr)oxides in AsUNT while the relation was the opposite, 2/3 iron and 1/3 aluminum (hydr)oxides in AsZVI which agrees well with the EXAFS interpretations.…”
Section: Immobilization Mechanismsmentioning
confidence: 99%
“…Arsenate is strongly bound as inner-sphere surface complexes to iron and aluminum (hydr)oxides in soils (Hopp et al, 2008;Violante and Pigna, 2002). Earlier investigations of ZVI-stabilized As-contaminated soil (Komarek et al, 2013;Mench et al, 2006) …”
Section: Introductionmentioning
confidence: 99%
“…Studying an industrially contaminated soil, Terzano et al (2007) reported that Cr was present largely as chromite. In a similar manner, Szulczewski et al (1997) examined contaminated soils from the United States and found that <10% was present as Cr(VI) in most samples, while Hopp et al (2008) examined a CCA contaminated soil and reported that Cr was present as Cr(III), either in a recalcitrant phase (such as residual CCA-treated wood) or in a mixed Fe(III)/Cr(III) solid phase. This reduction of Cr(VI) to Cr(III), such as during the remediation of a contaminated soil, can occur due to the influence of organic matter.…”
Section: Chromiummentioning
confidence: 98%
“…The untreated soil contains substantial amounts of Fe and 2% organic matter. Arsenic has been shown to co-locate with Fe, Cr, Cu and Zn-Fe in CCA-contaminated soil (Gräfe et al 2008;Hopp et al 2008) and combines with Zn to form adamitelike and koritnigite-like precipitates on goethite surfaces (Gräfe and Sparks 2005). Zn is a rather mobile element in acidic and oxidised soils (McBride 1994).…”
Section: Contaminants In the Studied Soilmentioning
confidence: 99%